Tingkat Kecemasan Ibu Post Partum Primipara dalam Proses Menyusui Bayi di Wilayah Kerja Puskesmas Siak Hulu II - Chairil; Isnaniar; Norlita, Wiwik; Aulia Septi Ayu (As-Shiha: Jurnal Kesehatan, 2024)
Maternal anxiety is a psychological impact experienced by mothers during and after childbirth. Breastfeeding is a common activity done by mothers to their children. Obstacles to breast milk production may be caused by discomfort, tension, anxiety and pain. Objective This study was to determine the level of anxiety of primiparous postpartum mothers in breastfeeding. Methods Used in this study is a quantitative descriptive method, carried out on March 02 to 10, 2024 in the Siak Hulu II Health Center Working Area. The population in this study amounted to 30 primiparous post partum mothers in the Siak Hulu II Health Center Working Area using the total sampling method. Data collection techniques using questionnaires and data analysis used are univariate. The results of the study were obtained based on the characteristics of the lowest age of 20 years and the highest age of 32 years, based on the majority of the last education, namely high school (53.3%), based on the majority of occupations, namely housewives (80.0%), based on the majority of labor history, namely Sectio caesarea (73. 3%), based on the majority of postpartum days ranging from 31-40 days (66.7%) and the results of the anxiety level of primiparous postpartum mothers in the process of breastfeeding the baby There is no anxiety problem (36.7%), mild anxiety (16.7%), moderate anxiety (6.7%) severe anxiety (23.3%) and severe anxiety (16.7) Conclusion The anxiety level of some primiparous postpartum mothers in the process of breastfeeding in the working area of the Siak Hulu II health center has no anxiety problems. Suggestion It is expected that primiparous postpartum mothers know the readiness to become a mother, especially in breastfeeding the baby